Managing sustainable innovation - Ratten, Vanessa; Ramírez-Pasilla, Marcela; Lundberg, Hans (College teacher) (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book is an insightful text looking at sustainable innovation and the emerging fourth sector i.e. hybrid organizations through an interdisciplinary approach. The book illuminates what hybrid organizations are and how they generate new ways of creating blended value to secure the well-being of future generations and preservation of ecological services. The book also discusses how sustainable innovation may offer creative solutions to societal issues, the sharing economy and the circular economy. This book will appeal to those taking MBA, EMBA programmes and those with an interest in creating sustainable business and innovation solutions"--
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable development -- Social aspects; Technological innovations -- Social aspects; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Leadership